POTENTIAL OF DUTCH TEAK LEAVES (Guazuma ulmifolia) AS ANTIOXIDANTS AND ANTI-INFLAMMATORIES AGENT - Smaradhna, Safira; Az Zahra, Zaviera; Maria Sidabutar, Carolina; Eskalatin, Khaira; Tamzil, Nia Savitri; Lusiana, Evi; Oktariana, Desi; Dwi Prasasty, Gita; Parisa, Nita (International Islamic Medicine Forum, 2023)
Oxidative stress is an imbalance in the quantity of reactive species and antioxidant activity that is often associated with inflammatory diseases. Inflammation is the main cause of morbidity in most of the world's population. Inflammation occurs when there is an invasion of foreign bodies and pathogenic agents such as bacteria, parasites, and viruses that cause activation of the immune system. The protective effect of the inflammatory process is actually very good under normal circumstances. However, in chronic inflammation, tissue damage becomes uncontrollable and can lead to various diseases such as rheumatoid arthritis, multiple sclerosis, inflammatory bowel disease, psoriasis and neoplastic transformation. For inflammatory therapy, steroids and non-steroidal drugs (NSAIDs) are usually used, but the use of these drugs can have serious long-term effects. Therefore, the development of anti-inflammatory agents from natural sources such as certain plant species that are safe, efficacious, biocompatible and cost-effective is a rational strategy that can be used to treat inflammatory diseases. One of its species, Guazuma ulmifolia or Dutch teak plant, is widely used in traditional medicine because it contains bioactive compounds, especially proanthocyanidins and flavonoids which have anti-oxidant and anti- microbial properties. The leaves and flowers of Guazuma ulmifolia can be used in fever, gastrointestinal disease, kidney disease and diabetes. Guazuma ulmifolia can protect the gastric mucosa against the harmful effects of NSAIDs through anti-inflammatory and anti-oxidant mechanisms. The extract of Dutch teak leaves (Guazuma ulmifolia) was also effective in reducing the expression of myeloperoxidase in the pulmonary tissue of Wistar white rats with pulmonary contusions .